Beyond thyroid dysfunction: the systemic impact of iodine excess - Khudair, Aiman; Khudair, Ahmed; Niinuma, Sara Anjum; Habib, Haniya; Butler, Alexandra E. (Frontiers in Endocrinology, 2025)
As an essential micronutrient, iodine plays a crucial role in several physiological systems, particularly in the production of thyroid hormone. While deficiency is widely recognized, the consequences of iodine excess (IE) are less studied. IE, which may be caused by iodine-rich diets, supplements, iodinated contrast media and salt iodization, has been implicated in a range of adverse outcomes on thyroid and systemic health. Examples include autoimmune thyroid diseases like Graves’ disease and Hashimoto’s thyroiditis, driven by immune cell polarization and gut microbiota alterations. Furthermore, excessive iodine intake is associated with increased risks of cardiovascular diseases, including hypertension and atherosclerosis, due to oxidative stress, inflammation, and endothelial dysfunction. It contributes to the development of thyroid cancer, particularly papillary thyroid cancer, through genetic mutations such as BRAF mutations and enhanced cancer cell proliferation. Excess iodine intake has been implicated to have neurotoxic effects, significantly impairing learning and memory, negatively impacting neonatal brain development, and potentially contributing to the progression of neurodegenerative conditions. It also has a potential role in renal dysfunction in vulnerable populations, due to overload from povidone-iodine in sterile equipment. This mini-review aims to collate the adverse effects of IE, beyond its effect on thyroid health, through investigation of the cardiovascular, nervous, and renal systems. Through our consolidation of the current literature, we hope to raise awareness and contribute to the understanding of the multifaceted impact of excessive iodine intake.